Cadmium tolerance and phytochelatin content of Arabidopsis seedlings over-expressing the phytochelatin synthase gene AtPCS1 - Brunetti, Patrizia (Oxford University Press, 2011)
Previous studies demonstrated that expression of the Arabidopsis phytochelatin (PC) biosynthetic gene AtPCS1 in Nicotiana tabacum plants increases the Cd tolerance in the presence of exogenous glutathione (GSH). In this paper, the Cd tolerance of Arabidopsis plants over-expressing AtPCS1 (AtPCSox lines) has been analysed and the differences between Arabidopsis and tobacco are shown. Based on the analysis of seedling fresh weight, primary root length, and alterations in root anatomy, evidence is provided that, at relatively low Cd concentrations, the Cd tolerance of AtPCSox lines is lower than the wild type, while AtPCS1 over-expressing tobacco is more tolerant to Cd than the wild type. At higher Cd concentrations, Arabidopsis AtPCSox seedlings are more tolerant to Cd than the wild type, while tobacco AtPCS1 seedlings are as sensitive as the wild type. Exogenous GSH, in contrast to what was observed in tobacco, did not increase the Cd tolerance of AtPCSox lines. The PC content in wild-type Arabidopsis at low Cd concentrations is more than three times higher than in tobacco and substantial differences were also found in the PC chain lengths. These data indicate that the differences in Cd tolerance and in its dependence on exogenous GSH between Arabidopsis and tobacco are due to species-specific differences in the endogenous content of PCs and GSH and may be in the relative abundance of PCs of different length.